The meaning of entrance and scenery spaces in the Lithuanian architecture of public buildings of 1960–1980s - Novickas, Audrius (Journal of Architecture and Urbanism, 2012)
The paper explores the meaning of bridges, stairways, ramps as well as terraces, balconies, glass facades as emphasized in most important examples of Lithuanian modern architecture of 1960–1980s. These architectural elements are looked at as constitutive in design of entrance and scenery spaces of the public buildings of the period. The assumption is made that analysis of entrance and scenery spaces is instrumental in interpreting the program aspects of Lithuanian architecture of Soviet period in the broader contexts of modern paradigms, aims of the political system and aspirations of individual architects. The research is aimed to reveal the entrance and scenery space formats as embodying the architecture of power effects, signifying the system to discipline and control as well as skills of individual architects to embody sublime environments of aesthetic experience.Article in Lithuanian.Įeigų ir regyklų reikšmė Lietuvos XX a. 7–9 dešimtmečių visuomeninės paskirties pastatų architektūrojeSantrauka. Straipsnyje nagrinėjama tiltų, laiptų, rampų, atvirų terasų ir balkonų, įstiklintų fasadų reikšmė svarbiausių XX a. 7–9 dešimtmečių Lietuvos visuomeninės paskirties pastatų architektūroje. Šie elementai tiriami kaip formuojantys pastatų įeigas ir regyklas. Daroma prielaida, kad įeigų ir regyklų analizė teikia pagrindą interpretuoti Lietuvos sovietinių metų moderniosios architektūros programinius aspektus platesniame epochos paradigmų, sistemos politinių tikslų ir individualių architektų meninių aspiracijų kontekste. Siekiama atskleisti, kad įeigos ir regyklos rodo visuomeninius pastatus esant kokybinio pokyčio proceso ir galios efektų erdvėmis, įkūnijančiomis ne tik sistemos siekį disciplinuoti ir kontroliuoti, bet ir architekto gebėjimą formuoti mėgavimosi estetiniais architektūros aspektais aplinkas.Reikšminiai žodžiai: visuomeninės paskirties pastatų architektūra, sovietinių metų modernizmas, įeiga, regykla, perėjimo procesas, galios žvilgsnis.